Structural, Thermal, and Release Properties of Hybrid Materials Based on Layered Zinc Hydroxide and Caffeic Acid - Ruiz Madronero, Christhy; et al. (Nanomaterials, 2020)
Caffeic acid (CA) molecules were immobilized in a layered inorganic host matrix based on zinc hydroxide structures with different starting interlayer anions, nitrate, and acetate. The chemical composition, structure, thermal stability, morphology, and surface of the host matrices and hybrid compounds were analyzed by X-ray diffraction (XRD), themogravimetric/differencial thermal analysis (TG/DTA), Fourier transform infrarred spectroscopy (FT-IR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). Additionally, the surface charge of the materials was investigated using zeta potential at pH 7. The results show an influence of the surface charge on the chemical, interaction, and structure of the resulting hybrid materials as a function of the starting layered structures. An expansion of the basal spacing to 10.20 Å for zinc hydroxide nitrate (ZHN), and a shrinkage to 10.37 Å for zinc hydroxide acetate (ZHA). These results suggest that the CA lies with a tilt angle in the interlayer region of the inorganic host matrix. The immobilization of CA is favored in ZHN, with respect to ZHA, because a single-layered phase was identified. A higher thermal stability at 65 °C was observed for ZHN-CA than for ZHA-CA. The evaluation of the release behavior showed a higher percentage of CA released from ZHN than ZHA, and the release mechanism was described by the Elovich model. The hybrid materials show potential characteristics for use as bioactive delivery systems.<br
Keywords: layered zinc hydroxide; caffeic acid; hybrid material; release systems; immobilization